Methodology for implementing power plant efficiency standards for power generation: potential emission reduction - Mahlia T.M.I.; Lim J.Y.; Aditya L.; Riayatsyah T.M.I.; Pg Abas A.E.; Nasruddin (Springer Verlag, 2023)
Costs; Electric utilities; Emission control; Energy efficiency; Energy policy; Fossil fuel power plants; Gas emissions; Greenhouse gases; Greenhouses; Life cycle; Natural gas; Power generation; Efficiency standards; Emission reduction; Energy efficiency standards; Greenhouse emissions; Lifecycle costs; Power generation plants; Power plant efficiency; Techno-economics; Natural gasoline plants